Au(III) complexes with tetradentate-cyclam-based ligands - Reiersølmoen, Ann Christin; Solvi, Thomas N.; Fiksdahl, Anne (Beilstein Journal of Organic Chemistry, 2021)
Chiral cyclam (1,4,8,11-tetraazacyclotetradecane) derivatives were synthesized stepwise from chiral mono-Boc-1,2-diamines and (dialkyl)malonyl dichloride via open diamide-bis(N-Boc-amino) intermediates (65–91%). Deprotection and ring closure with a second malonyl unit afforded the cyclam tetraamide precursors (80–95%). The new protocol allowed the preparation of the target cyclam derivatives (53–59%) by a final optimized hydride reduction. Both the open tetraamine intermediates and the cyclam derivatives successfully coordinated with AuCl3 to give moderate to excellent yields (50–96%) of the corresponding novel tetra-coordinated N,N,N,N-Au(III) complexes with alternating five- and six-membered chelate rings. The testing of the catalytic ability of the cyclam-based N,N,N,N-Au(III) complexes demonstrated high catalytic activity of some complexes in selected test reactions (full conversion in 1–24 h, 62–97% product yields).
Keywords: Au(III); carboalkoxylation; coordination studies; cyclam derivatives; cyclopropanation